2005
DOI: 10.1016/j.cardiores.2004.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Vascular consequences of menopause and hormone therapy: Importance of timing of treatment and type of estrogen

Abstract: Premenopausal women have a lower risk for cardiovascular events, and mortality due to coronary vascular disease (CVD) in premenopausal women is rare. These facts suggest that endogenous estrogens, such as estradiol, protect the cardiovascular system, and several observational studies and a few small clinical studies conducted in healthy and younger postmenopausal women support this hypothesis. In contrast, two large randomized clinical trials (RCTs), using conjugated equine estrogens and conducted in older wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
172
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(183 citation statements)
references
References 120 publications
8
172
0
3
Order By: Relevance
“…Since 17␤-estradiol administered during hormone replacement therapy will rapidly increase estrone sulfate after conversion in adipose tissue, hormone replacement therapy can have proinflammatory effects by providing estrone sulfate to the inflamed synovial tissue. This is particularly true when a crude mixture of estrogenic compounds is used with various estrone-derived estrogens (32). The preponderance of 16␣OH-estrone relative to other estrogens was not observed in the presence of 17␤-estradiol.…”
Section: Discussionmentioning
confidence: 99%
“…Since 17␤-estradiol administered during hormone replacement therapy will rapidly increase estrone sulfate after conversion in adipose tissue, hormone replacement therapy can have proinflammatory effects by providing estrone sulfate to the inflamed synovial tissue. This is particularly true when a crude mixture of estrogenic compounds is used with various estrone-derived estrogens (32). The preponderance of 16␣OH-estrone relative to other estrogens was not observed in the presence of 17␤-estradiol.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, some investigators have found no significant association between estrogen and lipid levels (17)(18)(19). Moreover, although menopausal transition increases insulin resistance (20) and arterial pressure (21), no data exist as to whether fluctuations in circulating estradiol within the menopausal range have any impact on these parameters. The same discrepancy holds for homocysteine metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…The matter is further complicated when studying the effect of exogenous estrogens on CVD risk factors and incidence in postmenopausal women. Although ample evidence exists that exogenous estrogens improve lipid-lipoprotein profile, insulin resistance, homocysteine metabolism, and vasodilation and that estrogens have anti-inflammatory properties at the vascular wall (21), the results of recent randomized controlled studies have revealed an increased risk of ischemic cardiac events in postmenopausal women treated with estrogen-progestin therapy (23).…”
Section: Introductionmentioning
confidence: 99%
“…11 For example, the Heart and Estrogen/progestin Replacement Study (HERS) 8 and the Women's Health Initiative (WHI) 6,7 study assessed the effect of treatment with conjugated equine estrogens, a mixture of estrogens extracted from horse urine that also contains progestins and androgens, whereas estradiol is the major endogenous estrogen. 12 Differences in the outcomes of epidemiological studies and clinical trials are best interpreted in the context of an understanding of the biological effects of estrogen. On the one hand, oral HRT increases circulating fibrin split products (FSP), concentrations of inflammatory cytokines, and C-reactive protein.…”
mentioning
confidence: 99%